A one-dimensional and two-phase flow model of a proton exchange membrane fuel cell - Rui B. Ferreira (2015)
BACKGROUND: Mathematical models are very important tools for the development of proton exchange membrane (PEM) fuel cells. In this work, a one-dimensional, steady-state and two-phase flow model of a PEM fuel cell is presented. RESULTS: The present two-phase flow model is able to predict the experimental results more accurately than its single-phase counterpart, especially for high current values. In addition, the model presented here also allows calculation of the threshold current density defining the boundary between single and two-phase regimes, which can be used to provide a set of operating conditions avoiding a high content of liquid water and the resulting negative effects on cell performance. CONCLUSIONS: Owing to its low demand on computational time, the proposed model can be used for PEM fuel cells system simulations, offering many advantages over empirical models. Â(c) 2015 Society of Chemical Industry.